PENGARUH KANDUNGAN AKTIF BUAH CABE JAWA (Piper retrofractum Vahl) terhadap KADAR TESTOSTERON TIKUS JANTAN GALUR WISTAR - Siti Muslichah (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2012)
This studi was aimed to isolate piperine from cabe jawa (Piper retrofractum Vahl) and to look at the effect of piperine and hexane-undissolved piperine free fraction on testosterone levels of male rats. The subject of this research were twenty five healthy male wistar rats., which every group consist of five rats. Every group was treated by orally administration with Andriol (Testosterone undecanoat) 0,72 mg , CMC-Na 1%, piperine 1,6 mg/kg bw, hexane-undissolved piperine free fraction 29,10 mg/kg bw and hexane-undissolved fraction 31,72 mg/kg bw twenty seven days period of time, once a day. At the end of treatment, testosterone concentration was measured using Enzime Linked-Immunosorbent Assay (ELISA) technique. Result were statistically evaluated by ANOVA followed by LSD test at the 0,05 significance level. The result of this studi showed that serum testosterone level was increased compared to the CMC-Na 1% group for hexane-undissolved piperine free fraction while piperine caused a decrease in the testosterone level. However, the increase and the decrease in values were not statistically significant (p>0,05).